Community-Based Mangrove Restoration for Coastal Ecosystem Sustainability: A Case Study of Mangrove Park Lampulo in Banda Aceh - Fadhilah, Nabila; Pranata, Eka Octavian; Febrita, Lyra Vellaniza; Smaradhani, Ika Indah (Perkumpulan Manajer Pendidikan Islam Indonesia (PERMAPENDIS) Prov. Sumatera Utara, 2025)
Mangrove ecosystems play a crucial role in maintaining coastal environmental sustainability by protecting shorelines from erosion, supporting marine biodiversity, and contributing to climate change mitigation. However, mangrove areas in many coastal regions continue to experience degradation due to environmental pressures and human activities. This community engagement program aimed to promote coastal ecosystem sustainability through a community-based mangrove restoration initiative conducted at Mangrove Park Lampulo in Banda Aceh, Indonesia. The program involved collaborative participation from 10 students of the Faculty of Islamic Economics and Business (FEBI) at UIN Ar-Raniry Banda Aceh, lecturers from the same institution, local community members from Pemangku Village, and several researchers from Badan Riset dan Inovasi Nasional. The activities were carried out through several stages, including environmental education, participatory mangrove planting, and simple monitoring of the planted mangrove seedlings. The results indicate that a community-based approach can increase environmental awareness among participants and strengthen collaboration between academic institutions, research organizations, and local communities in coastal conservation efforts. Furthermore, the mangrove planting initiative contributed to ecological restoration and encouraged greater community involvement in sustainable coastal environmental management. This study highlights the importance of collaborative and community-based approaches in promoting long-term mangrove conservation and coastal ecosystem sustainability.